“What’s the Harm in Being Unethical? These Strangers are Rich Anyway!” Exploring Underlying Factors of Double Standards - De Bock, Tine; Vermeir, Iris; Van Kenhove, Patrick (2013)
Previous studies show evidence of double standards in terms of individuals being more tolerant of questionable consumer practices than of similar business practices. However, whether these double standards are necessarily due to the fact that one party is a business company while the other is a consumer was not addressed. The results of our two experimental studies, conducted among 277 (Study 1) and 264 (Study 2) participants from a Western European country by means of an anonymous self-administered online survey, demonstrate that the respondents were not only harsher in their judgments of unethical business (vs. consumer) behavior, but also harsher in their judgments of unethical behavior by prosperous (vs. non-prosperous) consumers and prosperous (vs. non-prosperous) business companies (Study 1). Further, they were also less tolerant of unethical behavior by consumers (vs. one’s best friend) and business companies with which they have a less than good (vs. a good) relationship (Study 2). These results indicate that double standards are due to differences in perceived wealth between subjects and in the individual’s relationship with subjects. These two factors imply that double standards are not strictly reserved to consumer–business relations, but might also be used in business–business and consumer–consumer relations. Further, these results indicate that companies need to be aware of the fact that good financial figures may backfire as they might lead individuals to be more critical of a company’s deceptive practices. Moreover, these findings point to the importance of businesses investing resources—and to keep investing resources—in developing a good relationship with stakeholders as these good relationships lead to stakeholders being less prone to make moral condemnations.
Keywords: Wealth; Relationship; Moral hypocrisy; marketing ethics; ethical beliefs; double standards; Business Ethics; Consumer ethics